Attitude to health among athletes with extremities injuries - Malikova, L.; Yakovleva, N. (BIO Web of Conferences, 2020)
Attitude to health presents the inner mechanism of activity and behavior self-regulation. For a professional athlete positive attitude to health is the base for a successful career. However, the system of a personality`s attitudes is a dynamic construct. It is influenced by many factors, including sports injuries. During the research we tried to describe the peculiarities of health-protecting behavior, including the attitude to health of professional athletes with extremities injuries. In order to define the specific influence of sport as a professional activity we chose athletesamateurs with extremities injuries as the group of comparison. The results of the held research prove that the attitude to health is the main determinant of professional athletes health-protecting behavior and at the same time, it is not included into the model of health -protection of athletesamateurs. It reflects the influence of professional specificity in the system of personality`s attitudes formation.